Designing an Ethereum-based Blockchain for Tuition Payment System using Smart Contract Service - Moch Sholeh; Esther Yolanda Talahaturuson; Maulana Rizqi; Agustinus Bimo Gumelar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
The security and disclosure of information in online transaction data remain a sensitive subject until this day. Whenever data collection from a transaction process is accessible over the internet system, certain parties may misuse any one of these data. Blockchain technology, which includes the use of smart contracts, is thought to overcome this problem due to the blockchain's decentralized and distributed nature. Blockchain allows transaction data to be accessed openly and transparently while securely protected by hashing encryption owned by intelligent contracts. This enables users to have detailed access privileges to each transaction's data. The development of smart contracts will be carried out in the production of microservices payment gateways based on decentralized apps (DApps) on the Ethereum blockchain in this research, with the payment gateway generated being used in the tuition payment process. The Truffle framework and the Metamask wallet will be used to assist the Ethereum payment process during the DApps development process. Testing the functionality of each intelligent contract feature reveals that the payment system can be utilized effectively and that there are no issues that cause transaction failures.